Quantum π-Driven Predictive Chemistry: Applications to Reactivity, Electronic Structure, and Simulation-Based Forecasting - Barack Ndenga (Publisher, 2025)
I develop the concept of quantum π as a predictive invariant for chemical reactivity, electronic structure, and simulation-based forecasting. Building on my observation that π governs phase continuity, normalization, and standing-wave structure in quantum systems, I extend this framework to molecular chemistry, where π emerges naturally in delocalized electron networks, orbital topology, and reaction pathways. I propose that quantum π can serve as a unifying descriptor linking molecular symmetry, energetic spacing, resonance strength, and transition-state accessibility. Through analytical reasoning and simulation-inspired examples, I show how quantum π can be directly applied to predict stability trends, reaction outcomes, charge redistribution, spectroscopic signatures, and the energetic landscape of reactive intermediates. This article establishes quantum π as a foundational principle for predictive chemistry
This article develops a comprehensive framework for applying the quantum π-index as a predictive tool in chemical reactivity, molecular electronic structure, and mechanistic analysis. I demonstrate how the π-index captures subtle variations in π-electron delocalization and provides quantitative insight into site-selective reactivity across aromatic, heteroaromatic, and conjugated systems. Through detailed simulations, comparative energetics, frontier-orbital correlations, and reaction-coordinate analysis, the π-index emerges as a robust and generalizable descriptor for predicting chemical behavior. The results confirm that the π-index not only reproduces known experimental trends but also anticipates reactivity patterns in unexplored or theoretically constructed molecular systems, offering a powerful tool for advanced molecular design and computational chemistry. This publication forms a central part of the broader “Quantum π Chemistry Series,” establishing π as an informational and structural constant underlying molecular reactivity.